Exploring Teachers’ Perspectives on Leadership Regeneration in Muhammadiyah Schools: A Phenomenological Study - Hasanah, Enung; Al Ghazi, M. Ikhsan (International Journal of Learning Reformation in Elementary Education, 2025)
Leadership regeneration in educational institutions plays a crucial role in ensuring long-term sustainability. In Muhammadiyah schools, this system is expected to embody the values of transparency, justice, and professionalism. Although such a system is in place, there is limited research on how teachers, as essential stakeholders, perceive and experience the process. This study explores the meanings attached to the leadership regeneration system by drawing on the experiences of nine Muhammadiyah teachers. Using a phenomenological approach, the research collected and analyzed data to uncover underlying perceptions. Overall, participants conveyed a generally positive attitude toward the system, though a few expressed minor dissatisfaction. Analysis revealed four key themes from the teachers’ narratives: transparency in leadership selection, which highlights the need for openness in decision-making; fairness and justice, emphasizing the importance of equitable treatment during transitions; a sense of care and support for teachers, showcasing leadership’s role in nurturing a positive environment; and motivation and professional growth, illustrating the system’s influence on teacher enthusiasm and career advancement. These findings highlight the importance of a well-designed leadership regeneration system in promoting teacher satisfaction and supporting the ongoing vitality of educational institutions.